Navigating the Frontier: Assessing the Extent of AI's Influence in Healthcare - Erizo, Juan Jacob (PT. Lentera Ilmu Publisher, 2024)
This study explores the integration of Artificial Intelligence (AI) into healthcare, examining its applications across various domains, including diagnostic imaging, personalized medicine, predictive analytics, and administrative workflows. AI has demonstrated significant potential to enhance the accuracy, efficiency, and accessibility of medical services. For instance, AI-driven diagnostic tools improve cancer detection, while AI in personalized medicine tailors treatments based on genetic data. However, challenges such as ethical concerns, data privacy, and the